Um estudo das metáforas no léxico do caranguejo no Maranhão: São Luís e Araióses - Araujo, Luciana Moreira de (2017)
The present study, which is part of Cognitive Linguistics, aims to identify and analyse the metaphorical formations which exist in the crab's lexicon in Maranhão. This study was inspired by the interest to verify the recurrance of metaphorical formations in the language spoken by the professionals in that universe, in a labor context, given the fact that various studies have shown such recurrance in other knowledge domains, like the work of Costa (2007), Maciel e Silva (2010), Oliveira (2011), etc. The analysed corpus consists of 14 interviews produced between 2007 and 2008 in São Luís/MA and Araioses/MA, executed with men whose work is to capture the crabs in the mangrove and/or to sell the product, and also with women who are responsible for removing the already cooked and ready for commercialization crab's flesh. It’s worth noting that some denominations were designated to the three kinds of activity mentioned above, respectively: catação (capture), comercialização (commercialization) and processamento de caranguejo (processing of the crab). These interviews are also part of a scientific initiation research, developed by the author of this dissertation, during the undergraduate program in Letras, which had as the main target the construction of the Glossário de Termos do Universo do Caranguejo: São Luís e Araioses, also handled and analysed while the study, which is now presented here, was being completed. This research is done according to the methodological assumptions of the Conceptual Metaphor Theory, created by George Lakoff and Mark Johnson (1986), who affirm that our conceptual system is widely metaphorical and plays a nuclear role in the definition of our everyday realities. The data reveal that the metaphors are present in the speaking of the professionals and that the lexical units of the crab’s universe find motivation in the similarity that exists between objects of the human dayly life and the culture itself of the people involved with the universe under study, like the metaphorical lexical units nipper and forceps, in which we notice a conceptual relation established between the nipper and forceps (from the domain of the tools) with the nipper and forceps (crab's claws), among other metaphors.